Rethinking ‘errors’: Patterns of grammatical productivity in young Spanish-English bilinguals - Potapova, Irina; Gallagher, John; Escobedo, Alicia; Pruitt-Lord, Sonja (Journal of Monolingual and Bilingual Speech, 2023)
All children produce non-adult-like grammatical forms (e.g., omissions, substitutions) in the process of acquiring the language(s) in their environment. Often, use of these forms is part of typical language development; in other cases, non-adult-like forms are indicative of developmental language disorder (DLD). For children acquiring multiple languages, additional variability in language use is expected, as their experiences with each language vary. For accurate assessment in speech-language pathology, measures must differentiate typical and atypical development within the variability of dual language learning. Recent research indicates that measuring productivity – or the diversity and flexibility of children’s morphosyntactic skills – may be helpful in meeting this need: across speaker populations, typical language development is characterised by relatively greater productivity. However, available work has largely prioritised productivity within accurate productions. Presently, we ask: what are patterns of productivity in the context of non-adult-like forms in the spontaneous language samples of preschool-aged Spanish-English bilinguals? Analyses were conducted in both languages, and, as predicted, typically developing bilinguals (n = 15; age range = 3;11-4;11 [years;months]) produced non-adult-like forms that demonstrated productivity, or the (over)use of grammatical markers (e.g., substitutions, overregularisations) in both Spanish and English. Conversely, non-adult-like forms produced by three bilingual peers with DLD (ages 3;10, 4;1 and 4;3) were primarily characterised by limited productivity (i.e., omissions). Patterns observed here align with previous research and with the profile of DLD, in which children demonstrate difficulty learning and using grammatical markers. Additionally, present findings revealed cross-linguistic differences in productivity across English and Spanish, likely stemming from differences in grammatical structures between languages and, relatedly, differences in grammatical forms prioritised in assessment for each language. Present findings motivate further work in descriptive analyses of language use (i.e., identifying productive vs. non-productive forms) to improve our understanding of bilingual language development and to support clinical decision-making.